Brachial plexus block for the resection of a chondrosarcoma during COVID-19: A case report - Ehssan Mohamed; Hassan Elbahri (Health and Social Sciences Research Institute - South Sudan (HSSRI-SS), 2023)
A case report of a 35-year-old female with a large low-grade chondrosarcoma of the left humerus. Resection was performed under regional anaesthesia (interscalene brachial plexus block): this is a useful technique where there are limited resources and during the COVID-19 pandemic.